Does industrial relocation affect regional carbon intensity? Evidence from China's secondary industry. (February 2023) - Lin, Boqiang; Wang, Chonghao
Abstract: Over the past 20 years, China has experienced several waves of secondary industry relocations, where some secondary industries move from one region or province to another. Variant from the primary industry and the tertiary industry, the secondary industry (mainly the industrial sectors) is made up of numerous energy-intensive firms and hence, have critical impacts on the regional carbon intensity. However, there is little knowledge about the structure of the secondary industry's relocation and its impact on carbon intensity. Based on the latest multi-regional input-output (MRIO) table, this paper measures the scale, trend and structure of the secondary industry's relocation between eight regions in China. The effect of the secondary industry's relocation on regional carbon intensity is discussed by applying GMM techniques to the panel data on the interregional industrial relocation across 30 provinces. The results confirm that the inflow of secondary industry positively affects the carbon intensity, which is stronger in the central regions. In addition, the heterogeneity analysis shows that implementing the "Belt and Road" Initiative enhances the impact of the secondary industry's relocation on carbon intensity. This paper deepens the understanding of the environmental effects of industrial relocation. Highlights: We estimate the industrial relocation between China's 30 provinces. The inflow of secondary industry tends to increase the regional carbon intensity. The inflow of secondary industry has the greatest impact on the central provinces. The Belt and Road initiative enhances the impact of secondary industry. The environmental impact of industrial relocation should be taken seriously.